(untitled) - Dymoke, Sue; Dymoke, Sue (London ; New York, 2015)
Includes bibliographical references (pages 197-213) and index; Making Poetry Matter draws together contributions from leading scholars in the field to offer a variety of perspectives on poetry pedagogy. A wide range of topics are covered including: - Teacher attitudes to teaching poetry in the urban primary classroom - Digital poetry and multimodality - Resistance to poetry in Post-16 English Throughout, the internationally recognised contributors draw on case studies to ensure that the theory is clearly linked to classroom practice. They consider the teaching and learning challenges that poetry presents for those working with learners aged between 5 and 19 and explore these challenges with reference to reading; writing; speaking and listening and the transformative nature of poetry in different contexts
Keywords: Poetry -- Study and teaching; Thơ -- Dạy và học